Perisynaptic Schwann cells phagocytose nerve terminal debris in a mouse model of Guillain‐Barré syndrome. Issue 2 (20th April 2020) - Cunningham, Madeleine E.; Meehan, Gavin R.; Robinson, Sophie; Yao, Denggao; McGonigal, Rhona; Willison, Hugh J.
Abstract: In mouse models of acute motor axonal neuropathy, anti‐ganglioside antibodies (AGAbs) bind to motor axons, notably the distal nerve, and activate the complement cascade. While complement activation is well studied in this model, the role of inflammatory cells is unknown. Herein we aimed to investigate the contribution of phagocytic cells including macrophages, neutrophils and perisynaptic Schwann cells (pSCs) to distal nerve pathology. To observe this, we first created a subacute injury model of sufficient duration to allow inflammatory cell recruitment. Mice were injected intraperitoneally with an anti‐GD1b monoclonal antibody that binds strongly to mouse motor nerve axons. Subsequently, mice received normal human serum as a source of complement. Dosing was titrated to allow humane survival of mice over a period of 3 days, yet still induce the characteristic neurological impairment. Behaviour and pathology were assessed in vivo using whole‐body plethysmography and post‐sacrifice by immunofluorescence and flow cytometry. ex vivo nerve‐muscle preparations were used to investigate the acute phagocytic role of pSCs following distal nerve injury. Following complement activation at distal intramuscular nerve sites in the diaphragm macrophage localisation or numbers are not altered, nor do they shift to a pro‐ or anti‐inflammatory phenotype. Similarly, neutrophils are not significantly recruited. Instead, ex vivo nerve‐muscle preparations exposed to AGAb plus complement reveal that pSCs rapidly become phagocytic and engulf axonal debris. These data suggest that pSCs, rather than inflammatory cells, are the major cellular vehicle for axonal debris clearance following distal nerve injury, in contrast to larger nerve bundles where macrophage‐mediated clearance predominates.